Pengaruh Peran Bundo Kanduang dan Budaya Lokal dalam Perkembangan Kelompok Tenun Padi Sarumpun Nagari Sungai Jambur Kabupaten Solok - Novita Fitri, Desri; Yeni, Afni; Roza, Seflidiana (STAI Denpasar Bali, 2023)
This study aims to examine the influence of the role of Bundo Kanduang and local culture in the development of the Tenun Padi Sarumpun, Sungai Jambur,. While the type of research used is quantitative research with a descriptive approach. The type of data used is primary data and the source of data used in this study is a questionnaire. This research has three variables consisting of 2 independent variables, namely the role of Bundo Kanduang and Local Culture and one dependent variable, namely the development of the Tenun Padi Sarumpun. The data analysis method used is multiple linear regression analysis.The results of this study indicate that (1) the role of Bundo Kanduang (X1) partially has no effect on the development of the Tenun Padi Sarumpun. This is evidenced by using the t test with a tcount value of 0.946 < 2.048 with a significance of 0.352 > 0.05. So that H1 is rejected (2) Local Culture (X2) partially influences the development of the Tenun Padi Sarumpun. This is evidenced by using the t-test with a tcount of 3.889>2.048 with a significance of 0.001<0.05. So H2 is accepted. (3) The results of the F test indicate that the role of Bundo Kanduang and local culture simultaneously or jointly affects the development of the Tenun Padi Sarumpun. This is evidenced by using the F test with an Fcount of 9.058 > 3.33 with a significance of 0.001 < 0.05. So H3 is accepted.